Investigations of bare frame behaviour for aspect ratio, storey and bay effect in the context of non-integral infilled frames - A.K., Gupta; Hampali, Mohankumar P. (Journal of Structural Engineering, 2025)
As an integral part of behavioural study of non-integral infilled frames for lateral loads, extensive experimentation is carried out on bare frames using hollow steel frame section. The hollow steel frame having width and depth 1” is adopted to configure the frames of different aspect ratio. Apart from conducting experiment on a single storey single bay reduced scale model for different aspect ratio, the frames are also studied for the addition of a bay of same width and addition of a storey of same height as it has been found that the lateral stiffness of a non-integral infilled frame is significantly varied due to number of bays and stories present in the structure. In order to appreciate the infill contribution, the bare frame action alone needs to be considered. The present paper explores the bare frame behaviour in single storey, two storey constructions with single bay and double bay along with the effect of aspect ratio in single storey non-integral infilled frames.